Disseminated histoplasma and CMV infection presenting as subacute intestinal obstruction in an immunocompromised patient - Shahani, Lokesh (BMJ Publishing Group, 2012)
Histoplasma in patients with impaired cellular immunity can disseminate to various organs and is known as progressive disseminated histoplasmosis. Similarly cytomegalovirus (CMV) is the most common opportunistic pathogen in an immunocompromised host. The authors report an older male with symptoms and radiological evidence of subacute intestinal obstruction. The patient had concerns for compromised immune system as he was on chronic prednisone and methotrexate therapy. Follow-up colonoscopy revealed a stricture in the proximal ascending colon. Biopsy of the stricture revealed ulcer with granulomatous inflammation including well-formed granulomas and an infiltrate of histiocytes within the lamina propria. Special stains on the specimen showed fungal structures consistent with Histoplasma capsulatum. Immunochemistry showed presence of CMV in the tissue. The patient had good response to antimicrobial therapy and did not have progression of intestinal obstruction. This case highlights the need to consider infectious pathology in immunocompromised patients presenting with obstructive symptoms.